Industrial Revolution 4.0 Contribution of chemical engineer (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The fourth industrial revolution is (IR 4.0) or in other words ‘Smart Industry’ that refers to technological evolution from automation of manufacturing processes to customized and flexible mass production technologies. Industrial revolution 4.0 is benefits chemical engineering by integrating combination of physical and digital technology into manufacturing chemical industries. By this combination, the productivity of the manufacturing plant can be  improved and risks of the process can be reduce which enhance the business operation. In order to integrate “what” into industrial revolution 4.0, chemical engineer is required system thinking which is understand on entire process and system of the chemical plant and make decision accurately, generate idea and troubleshoot the incident happened. Chemical engineers contribute to IR 4.0 by using smart manufacturing techniques to enhance productivity and expand revenue by R&D, smart products or services. In an enzymatic process, the process can be improved by introducing advanced analytic program to predict the optimum utilization of the machine and equipment.